2009
DOI: 10.1007/s10936-009-9133-3
|View full text |Cite
|
Sign up to set email alerts
|

Fast Mapping in Healthy Young Adults: The Influence of Metamemory

Abstract: Several research studies suggest the significant role played by metamemory in lexical abilities of both adults and children. To our knowledge, there have been no studies to date that have explored the role of metamemory (Judgments of Learning) in fast mapping of novel words by adults. One hundred and twelve undergraduate students were given tasks of fast mapping and judgments of learning. A one-way Multivariate Analysis of Variance revealed that participants who performed well on fast mapping had superior glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Fast mapping is then driven by learners’ innate curiosity for word learning. Adult language learners have been found to employ fast mapping as well, both when it comes to learning the meaning of nonwords (e.g., Ramachandra, Rickenbach, Ruda, LeCureux, & Pope, ) and incidental L2 word learning (e.g., de Vos, Schriefers, ten Bosch, & Lemhöfer, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast mapping is then driven by learners’ innate curiosity for word learning. Adult language learners have been found to employ fast mapping as well, both when it comes to learning the meaning of nonwords (e.g., Ramachandra, Rickenbach, Ruda, LeCureux, & Pope, ) and incidental L2 word learning (e.g., de Vos, Schriefers, ten Bosch, & Lemhöfer, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fast mapping is then driven by learners' innate curiosity for word learning. Adult language learners have been found to employ fast mapping as well, both when it comes to learning the meaning of nonwords (e.g., Ramachandra, Rickenbach, Ruda, LeCureux, & Pope, 2010) and incidental L2 word learning (e.g., de Vos, Schriefers, ten Bosch, & Lemhöfer, 2018). Second, Hulstijn (2003), citing Eysenck (1982, p. 203), argued that the processing activities that learners engage in might influence learning rates more than their intentions.…”
Section: Mechanisms Of Incidental Learningmentioning
confidence: 99%
“…These three principles are operative at the onset of lexical acquisition and help in acquiring early vocabulary. The principles which are more related to fast mapping are operative beyond early childhood, in older children and adults ( Golinkoff et al, 1992 ), and are utilized in consciously monitoring the learning of novel words ( Ramachandra et al, 2010 ). These three principles require the: (d) awareness of basic categories for generalization, (e) awareness of constraints on mapping novel names to nameless objects to meet mutual exclusivity, and (f) consideration of the use of conventional names for referents.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have tested FM in adulthood (8)(9)(10), with the tacit assumption being that this mechanism is specific to early developmental stages of language acquisition, enabling the prodigious rate of vocabulary expansion. These studies have shown that adults can learn verbal labels and facts through FM just as well as children (8,9).…”
mentioning
confidence: 99%